Translation Studies in China The State of the Art - Han, Ziman; Li, Defeng; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book features the latest research on translation by a dozen leading scholars of translation studies in China. The themes discussed are diverse, and include: translation policy, literary translation, medical translation, corpus translation studies, teaching translation, translation technologies, media translation, interpreting studies and so on. The contributors are all respected experts on their respective topics. The book reflects the state-of-the-art of translation studies in China, and offers a unique window on the latest thoughts on translation there.
Chapter 1 Translation studies as a Young Established Discipline in China -- Chapter 2 Chinese Discourse on Translation: Views and Issues -- Chapter 3 The Literary Obsession in Translation Studies in China: a Bibliometric Study Based on Chinese Translators Journal and Babel -- Chapter 4 Modernization through Translation: A Study of Science Translation in China (1890s - 1900s) -- Chapter 5 Translation Policy Studies in China: Review and Reflections -- Chapter 6 Interpreting Training in China: Practice and Research -- Chapter 7 The Development of Translation and Interpreting Curriculum in China's Mainland: A Historical Overview -- Chapter 8 Interpreting Studies by Chinese Scholars (1949- ) -- Chapter 9 A Bibliometrical Analysis of Corpus-based Interpreting Studies in China - Based on A Database of Articles Published in the CSSCI Journals (2007-2017) -- Chapter 10 Using Human-Intervened MT in the Translation of Literary and History Books -- Chapter 11 On the Construction of E-learning Platform for Translation Instruction Featured with Knowledge Systems -- Chapter 12 A Bibliometrical Analysis of Journal Articles on Military Translation Studies in China: 1982-2017 -- Chapter 13 Interpreting in POW Camps in the Korean War: The Case of Zhang Zeshi -- Chapter 14 The Journey of Ulysses to China's Mainland -- Chapter 15 Audiovisual Translation Studies in China: A Long Journey to Academic Acknowledgement -- Chapter 16 A Study on the Translating Principles of Traditional Chinese Philosophical Classics.
Keywords: Translating and interpreting; Comparative literature; Culture -- Study and teaching; Language Translation; Comparative Literature; Cultural Studies